Micro-TESE Outcomes for Non-Obstructive Azoospermia — The First Australian Series - Daniel LANTSBERG; Yossi MIZRACHI; Darren KATZ (Fertility & Reproduction, 2022)
Background: Micro-dissection testicular sperm extraction (micro-TESE) for non-obstructive azoospermia (NOA) was shown to achieve the best sperm retrieval rate (SRR) compared to other techniques. However, to date there is no large series of published Australian data. Aim: To study the incidence and predicting factors of successful sperm extraction in men with NOA undergoing micro-TESE in Victoria. Method: We retrospectively analyzed the clinical data of all consecutive patients with confirmed NOA who were treated between August 2014 and April 2020 in a single medical centre in Melbourne, Victoria. None were excluded. Patients underwent micro-TESE and upon a successful sperm retrieval, sperm was either frozen for fertility preservation or used fresh for ICSI. Results: During the study period, 85 men with NOA underwent micro-TESE in our centre. The overall sperm retrieval rate (SRR) was 61.2% (52/85). All patients with a history of surgically treated cryptorchidism or childhood diseases had a successful sperm retrieval. Patients with Kleinfelter syndrome had a 75% SRR. Patients with Idiopathic NOA and patients with a history of chemotherapy had a 50% and 40% SRR, respectively. Among the different types of testicular pathology, the highest SRR was found in men with complete hyalinization (100%). Hypospermatogenesis was associated with a high SRR of 93.3%, while Sertoli-cell-only histology was associated with only 46.3% SRR. The SRR has significantly increased from 33.3% in 2015-2016 to 73.6% in 2019-2020 (p=0.003). On Multivariate logistic regression analysis, baseline FSH levels <20 IU and history of childhood disease or Klinefelter syndrome were significantly associated with successful sperm retrieval. The cumulative pregnancy rate was 23.7%. Conclusion: This first report from Australia indicates that micro-TESE is an effective method for the treatment of NOA with high SRR and pregnancy rate. Our results can help patient management and counseling.